2020
DOI: 10.1002/jsfa.11008
|View full text |Cite
|
Sign up to set email alerts
|

Field phenotyping and quality traits of grass pea genotypes in South Italy

Abstract: BACKGROUND: Grass pea (Laithyrus sativus L.) is a rustic plant whose seeds are rich in polyphenols and antioxidants, and it has been consumed as food by human beings since ancient times. This study was conducted in Italy between 2017and 2019 to evaluate, under field conditions, the stability of seed yield, biomass and 1000-seed weight (THS) and to assess the antioxidant composition and activity of 11 grass pea accessions.RESULTS: Analysis of variance revealed significant effects of the environment, accession a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Frimpong et al [47] found the same result for the Kabuli variety (r = −0.06, ns). The relationship between SY and protein content for Kabuli chickpea is similar to that reported in the case of fava beans and grass pea by several studies [49][50][51]. The absence of correlation in the Kabuli chickpea accession could probably be attributed to the capacity of some chickpea accession, due to the fixation of biological nitrogen.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Frimpong et al [47] found the same result for the Kabuli variety (r = −0.06, ns). The relationship between SY and protein content for Kabuli chickpea is similar to that reported in the case of fava beans and grass pea by several studies [49][50][51]. The absence of correlation in the Kabuli chickpea accession could probably be attributed to the capacity of some chickpea accession, due to the fixation of biological nitrogen.…”
Section: Discussionsupporting
confidence: 87%
“…Zaccardelli et al [48] reported very similar results. The protein content values were lower for chickpea than the other leguminous species, such as grass peas, with values up to 24% [49]. In our study, the absence of the correlation between SY and protein content in Kabuli chickpea was demonstrated.…”
Section: Discussioncontrasting
confidence: 75%
“…Taking the above in consideration, grass pea breeding has focused mainly on enhancing yield and yield stability as well as on producing seeds with high nutritional value, meaning high protein and reduced β-ODAP content [29,90,91]. Both yield and quality are complex traits [30,92].…”
Section: Yield Vs Quality Stability In Grass Peamentioning
confidence: 99%
“…Additionally, Grela et al [99] found that grass pea seeds are rich in potassium (9.8 g kg −1 DM) and several minerals such as copper, zinc, iron, and manganese for which average levels were 5.1, 44.1, 62.1, and 23.7 mg kg −1 DM, respectively. Furthermore, grass pea is an interesting source of health-beneficial dietary lipids, with a high polyunsaturated fatty acid proportion (58%) and phenolic compounds with high antioxidant activity, such as an average value of 68 mg/100 g of Gallic acid [8,90,99,103].…”
Section: Grass Pea a Smart And Healthy Food Cropmentioning
confidence: 99%
See 1 more Smart Citation